Resolving the Sudan Crisis: A Critical Discourse Analysis of Norman Fairclough’s Perspective - Dhihyah, Dhihyah; Basid, Abdul; Yani, Achmad (Journal of Language and Literature Studies, 2025)
The conflict between South and North Sudan is worsened by racial differences. It has also destroyed public infrastructure, including healthcare. The healthcare system's collapse puts the Sudanese population at serious risk now and in the future. The purpose of this study is to reveal the text analysis dimension, the discourse practice dimension, and the sociocultural dimension in Sudan's famine news. A qualitative method is used as the foundational approach, with a critical paradigm as the research perspective. The approach used is Norman Fairclough's Critical Discourse Analysis (CDA) to uncover the relationships between language, power, and ideology in the discourse on the Sudan crisis. Data is collected from news articles discussing the Sudan crisis from multiple media, using manual recording tools and translation software to understand multilingual texts.The findings indicate that the choice of sentence structure reflects tense social relations within this conflict situation. The discourse created by the Sudanese government seeks to maintain legitimacy by diverting attention from internal issues like famine to external threats. Furthermore, the sociocultural dimension highlights the inability of international diplomacy to resolve the conflict, creating an impression of deadlock and underscoring the role of the international community in responding to Sudan's complex and historical crisis. Recommendations for future research include conducting field studies that involve perspectives from various groups and performing long-term analyses on the development of the Sudan crisis to understand the impact of government discourse within the context of dynamic socio-political change.